ANALYSIS OF VEGAPULS64 LEVEL TRANSMITTER USAGE IN PT ENERGI SEJAHTERA MAS - Willy Andreas; Andik Yulianto (ConCEPt - Conference on Community Engagement Project, 2022)
Email of correspondence: 1821006.willy@uib.edu, andik@uib.ac.id Abstract PT Energi Sejahtera Mas (ESM) is an oleochemical manufacturing company based in Dumai, Riau, Indonesia. PT ESM uses various instruments in their plants to support production processes. While author’s internship was underway, 3 level transmitters were replaced with VEGAPULS 64 in tank farms, which were on T-1225, T-1228, and T-1134 tanks.Analysis is performed on these three new level transmitters to see if VEGAPULS 64 is applicable on tank farms. Both new and old transmitters are compared by how much error they made while measuring medium’s height in tanks.The result shows that VEGAPULS 64 usage on T-1225 and T-1134 gives a more accurate measurement than the previous level transmitter. But, on the other hand, it causes more error on T-1228. There are some possibilities that might cause this to happen, which are wrong parameter adjustment, the signal’s polarization direction, or human error. Changing the parameter is recommended because the value is different with the one it supposed to be.